Meaningful experiences: innovative teaching activities (2020)
This is the first volume of the Meaningful Experiences where five teachers from Universidad Cooperativa de Colombia narrate their experiences as they decide to innovate in their everyday practice. To begin with, it is possible to perceive the scope of virtual reality in the classroom; then you can discover different opportunities for exportation; meanwhile, you can continue by closely understand the different resiliency processes of the child population who is a victim of the Colombian conflict; after that, you can comprehend the work with the community and how it is possible to solve the difficulties in their context, particularly with topics related to civil engineering; finally, you can learn about the involvement of social media in the teaching of law. All these experiences are quite different in their content, but they are similar as they have the purpose not only for innovation but also for sharing good practices in the teaching and learning processes with the community.